The Demand for Money and Monetary Adjustments in Chile - Hynes, Allan (Review of Economic Studies, 1967)
Journal Article The Demand for Money and Monetary Adjustments in Chile Get access Allan Hynes Allan Hynes University of Washington Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 3, July 1967, Pages 285–293, https://doi.org/10.2307/2296676 Published: 01 July 1967